Effect of Retinectomy with Pars Plana Vitrectomy in Proliferative Vitreoretinopathy: Surgical Success and Recurrence Rate (A Comparative Study): Doi: 10.36351/pjo.v40i3.1821 - Fazaa, Ali Abbas Hassan; Ghani Abdulla , Mudhher; Salman, Saad H. (Pakistan Journal of Ophthalmology, 2024)
Purpose: To assess anatomical and functional success of pars plana vitrectomy with retinectomy in cases of proliferative vitreoretinopathy (PVR grade C). Study Design: Retrospective chart review. Place and Duration of Study: AL-Ferdous Private Eye Hospital, Baghdad, from July, 2019- June, 2023. Methods: Thirty eyes of thirty patients with PVR grade C were included in the study. One group (n=15) underwent pars plana vitrectomy (PPV) without retinectomy, while the other group (n=15) underwent PPV with retinectomy. Complications, anatomic success, and visual acuity were documented and evaluated. The relationship between retinectomy duration and postoperative visual acuity was examined using a chi-square test, with a p-value less than 0.05 considered statistically significant. Results: Mean age of the patients was 46.13±13.95 years. Retinectomy group had 8 (53.3%) males and 7 (46.7%) females. The other group had 10 (66.7%) males and 5 (33.33%) females. In group 1 there were 5 phakic and 10 pseudophakic eyes while in group 2, there were 4 phakic and11 pseudophakic eyes. Postoperative complete retinal re-attachment was achieved in 100% eyes in retinectomy group. After six months, the first group had 5 eyes (33.3%) with improved visual acuity, stable visual acuity in 7 eyes (46.6%) and worsening of vision in 3 eyes (20%). For the second group, 8 eyes (53.3%) showed improvement, stability in 4 eyes (26.7%), and worsening vision in 3 eyes (20%) with p-value > 0.05. Conclusion: Retinectomy is beneficial in treating severe PVR and improves, ultimate retinal reattachment rate.